Study of Dissolution Enhancement of Furosemide by Solid Dispersion Technique Using Different Polymer - Tanvir Halim ,; Nilufa Haque ,; Md. Didaruzzaman Sohel ,; Rajibul Islam Khan ,; Mohammad Menhaj Ovi ,; Labiba Amal ,; Md. Hassan Kawsar, (Journal of Pharmacy and Nutrition Sciences, 2019)
The oral route of drug administration is the most common and preferred method of delivery due to convenience and ease of ingestion. The objective of this study is to determine the dissolution enhancement quality of various polymers to Furosemide. Furosemide was selected as the model drug because it is therapeutically extremely important, having very low aqueous solubility and dissolution rate, but they are well permeable through membranes of the gastro-intestinal tract. Solid dispersions of Furosemide were also prepared by fusion method and solvent evaporation method. In this study, the effectiveness of the two methods for furosemide was investigated and compared while the effect of polymer on the dissolution kinetics of the drug was also observed. Poloxamer (two grades of Poloxamer; poloxamer 188 and poloxamer 407 were used in this study ), PEG and HPMC were expected to raise the dissolution rate of the poorly water-soluble furosemide and given its good permeation through GI membrane, to increase their oral bioavailability. To enhance the dissolution and efficacy of furosemide, Poloxamer188, PEG6000, and HPMC 6cps were used in different quantities. This work examined the influence of polymers such as Poloxamer 188 & 407, PEG6000 and HPMC 6cps in different amounts on release profile of furosemide. Through the dissolution studies, the in vitro release profile of the drug formulations was evaluated. An improved in vitro dissolution was obtained in all the systems.